The influences of solar wind pressure and interplanetary magnetic field on global magnetic field and outer radiation belt electrons - J. Yu; L.Y. Li; J. B. Cao; G. D. Reeves; D. N. Baker; H. Spence (Geophysical Research Letters)
Abstract Using the Van Allen Probe in situ measured magnetic field and electron data, we examine the solar wind dynamic pressure and interplanetary magnetic field (IMF) effects on global magnetic field and outer radiation belt relativistic electrons (≥1.8 MeV). The dynamic pressure enhancements (>2 nPa) cause the dayside magnetic field increase and the nightside magnetic field reduction, whereas the large southward IMFs (Bz‐IMF < −2nT) mainly lead to the decrease of the nightside magnetic field. In the dayside increased magnetic field region (magnetic local time (MLT) ~ 06:00–18:00, and L > 4), the pitch angles of relativistic electrons are mainly pancake distributions with a flux peak around 90° (corresponding anisotropic index A > 0.1), and the higher‐energy electrons have stronger pancake distributions (the larger A), suggesting that the compression‐induced betatron accelerations enhance the dayside pancake distributions. However, in the nighttime decreased magnetic field region (MLT ~ 18:00–06:00, and L ≥ 5), the pitch angles of relativistic electrons become butterfly distributions with two flux peaks around 45° and 135° (A < 0). The spatial range of the nighttime butterfly distributions is almost independent of the relativistic electron energy, but it depends on the magnetic field day‐night asymmetry and the interplanetary conditions. The dynamic pressure enhancements can make the nighttime butterfly distribution extend inward. The large southward IMFs can also lead to the azimuthal expansion of the nighttime butterfly distributions. These variations are consistent with the drift shell splitting and/or magnetopause shadowing effect.